EKSPLORASI KERRABHAN SAPE: DARI KALELES DAN LINTASAN PACU KE IDE CRITICAL SPATIAL THINKING DALAM PEMBELAJARAN MATEMATIKA - Fani Nur Anggita; Indah Setyo Wardhani; Nilamsari Damayanti Fajrin; Richa Mulya Artikasari; Fatimatus Izzati Ramadianti; Farah Auliaulfattah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Kerrabhan Sape is full of critical spatial thinking activities because it involves the creativity of spatial objects from the installation of 'kaleles' (where the jockey controls the cow) in the pacu (race track). The purpose of this study is to explore the ideas of critical spatial thinking and mathematical ideas from Kerrabhan Sape culture so that they can be integrated into mathematics learning. The research method is qualitative research, with data collection techniques in the form of observation, documentation, and internet search. Data analysis is in the form of data reduction, data presentation, and drawing conclusions. The results of the study are in the form of critical spatial thinking ideas: (1) coding the characteristics of spatial objects, such as: describing the size, shape, position, and properties of the shape and comparing similarity, parallelism, and congruence in 'kaleles' and pacu track, (2) application of spatial objects in problem situations, such as: calculating, checking the validity of solutions, and assessing the effect of changes in size and position on the results in 'kaleles' and pacu track, (3) creativity of spatial objects, such as: designing innovative solutions by adding decorative ornaments to the cows and providing track barriers between pairs of cows. The mathematical ideas that emerge are: (1) angles, (2) midpoints, (3) similarity, (4) parallelism, (5) congruence, (6) geometry (flat shapes), (7) symmetry, (8) numbers (number operations), and (9) speed. In mathematics learning, these ideas play a role in explaining the concepts of numbers, geometry, and measurement.